2019
DOI: 10.3389/fimmu.2019.00064
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibodies Against C3b—Functional Consequences and Disease Relevance

Abstract: The complement component C3 is at the heart of the complement cascade. It is a complex protein, which generates different functional activated fragments (C3a, C3b, iC3b, C3c, C3d). C3b is a constituent of the alternative pathway C3 convertase (C3bBb), binds multiple regulators, and receptors, affecting thus the functioning of the immune system. The activated forms of C3 are a target for autoantibodies. This review focuses on the discovery, disease relevance, and functional consequences of the anti-C3b autoanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 53 publications
2
15
2
Order By: Relevance
“…Therefore, further studies are needed in order to clarify if anti-FB and anti-C3b autoantibodies have a primary mechanistic role in the pathology of the lipodystrophy or if they rather secondarily arise as a consequence of the increase in circulating complement proteins produced due to unabated complement activation in the presence of C3NeF. A plausible possibility in line with the presence of C3NeF and low C3 levels in our BSS cohort is that these autoantibodies synergistically promote further C3 convertase stabilization and C3 consumption in serum, similarly to what has already been described by Vasilev and colleagues for anti-C3 and anti-C3b autoantibodies in patients with lupus nephritis [33,34].…”
Section: Discussionsupporting
confidence: 75%
“…Therefore, further studies are needed in order to clarify if anti-FB and anti-C3b autoantibodies have a primary mechanistic role in the pathology of the lipodystrophy or if they rather secondarily arise as a consequence of the increase in circulating complement proteins produced due to unabated complement activation in the presence of C3NeF. A plausible possibility in line with the presence of C3NeF and low C3 levels in our BSS cohort is that these autoantibodies synergistically promote further C3 convertase stabilization and C3 consumption in serum, similarly to what has already been described by Vasilev and colleagues for anti-C3 and anti-C3b autoantibodies in patients with lupus nephritis [33,34].…”
Section: Discussionsupporting
confidence: 75%
“…We found that in some patients anti-properdin-positive IgG weakly increased the binding of properdin to C3b and to pro-convertase (C3bB), and did not affect the alternative complement pathway C3 convertase, unlike C3NeF, which reacted with C3 convertase and stabilized it [19]. In a case report of anti-properdin-positive IgG activated complement in serum [18], we did not detect fluid-phase complement activation by anti-properdin IgG, contrary to autoantibodies against other alternative pathway components, such as antifactor B, anti-C3b or anti-FH [29][30][31][32]. A possible explanation for the weak or absent effect of anti-properdin IgG could be the usage of low pH elution buffer for IgG purification, which may have a dramatic effect on the biological activity of IgGs and their antigen-binding behavior [33].…”
Section: Discussioncontrasting
confidence: 56%
“…Our studies showed decreased levels of C3 in the hippocampus of 18-months-old App KI mice. Complement activation leads to the production of functional fragments, with sequential cleavages from the conversion of C3, involved in phagocytosis via C3b opsonization and chemotaxis via C3a and C5a [ 98 ]. Thus, the decrease in C3 levels may be due to cleavage into fragments since the antibody used was against intact component C3 (185 kDa) but not the fragments, suggesting complement activation at 18 months in the App KI mice [ 94 ].…”
Section: Discussionmentioning
confidence: 99%